Exploratory Cross-Trial Non-Inferiority Analysis of 2% Versus 1% Sodium Hyaluronate in Knee Osteoarthritis - Fernando Costa; Pilar Coronel Granado; Laura Casas; Diego Maisonave Berdasco; Débora Renz Barreto Vianna (Journal of Clinical Medicine, 2026)
Objectives: Our primary objective was to compare the 12-month efficacy of two dosing regimens of intra-articular sodium hyaluronate (SH) in patients with knee osteoarthritis (OA) using a cross-study analysis within a non-inferiority framework. Methods: This study combined individual patient data from two prospective multicenter trials with similar outcome measures: the Trueba Davalillo study (five injections of 1% SH) and the SOYA Trial (single injection of 2% SH, with the possibility of retreatment after 6 months). The primary endpoint of this cross-study analysis was the relative change in pain intensity on a 100 mm visual analog scale (VAS) from baseline to 12 months. Secondary outcomes included changes in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the proportion of patients achieving the Minimal Clinically Important Improvement (MCII). Non-inferiority was defined for the primary endpoint as the lower bound of the 95% confidence interval for the between-group difference remaining above −8%. Results: The modified intention-to-treat (mITT) population included 97 patients in the 1% SH group and 98 in the 2% SH group. At 12 months, the mean relative reduction in pain intensity was 33.61% for 1% SH and 37.67% for 2% SH (mean difference: 4.06%; 95% CI: −6.37% to 14.50%), compatible with non-inferiority (per the predefined −8% criterion) in this exploratory cross-trial analysis. No significant between-group differences were found in adjusted analyses for pain or WOMAC scores at 12 months. At 12 months, MCII responder rates were higher in the 1% SH group. Conclusions: This exploratory cross-trial analysis found results compatible with non-inferiority of 2% SH relative to 1% SH in improving pain and physical function over 12 months in patients with knee OA.